Differential responses of the intestine and liver transcriptome to high levels of plant proteins in diets for large yellow croaker (Larimichthys crocea) - Ke, Qiaozhen; Li, Yin; Weng, Huasong; Chen, Baohua; Wang, Jiaying; Zhao, Ji; Jiang, Pengxin; Xu, Peng; Zhou, Tao (Frontiers in Genetics, 2025)
Large yellow croaker is an economically important carnivorous marine aquaculture fish in China with high protein requirements. Current fish meal - based feeds face issues like high cost and resource depletion, while plant protein sources have potential but also controversies. To explore this, a 120 - day feeding trial was conducted with a standard commercial feed (CF) and a modified feed (PF) where 70% of fish meal was replaced by plant protein. Results showed no significant growth performance differences between the two groups. Transcriptome analysis identified 557 and 308 differentially expressed genes in the liver and intestine respectively. GO and KEGG enrichment analyses indicated their association with immune response, lipid metabolism, and signal transduction. Five key genes related to metabolism and immune regulation were also found. These findings underscore the potential of integrating plant protein into fish diets, which could significantly enhance sustainable practices in global aquaculture while reducing reliance on fish meal. Emphasizing this transition is crucial for fostering environmental sustainability and supporting the future of aquaculture.